Tinjauan Prosedur Pengelolaan Kas Pada Biro Umum Dan Keuangan Badan Informasi Geospasial - Srihandoko, Wimpi; Yuliani, Renita; Muktiadji, Nusa (Jurnal Aplikasi Bisnis Kesatuan, 2023)
An organization in carrying out its activities definitely requires cash to finance these activities. Cash is the most liquid asset among other assets and plays an important role in the sustainability of the organization. Without cash, an organization will have difficulty meeting its short-term obligations, paying employee salaries, paying monthly utilities, and so on. For this reason, proper management is needed in order to optimize the use of cash. In the final project report which was prepared based on the drafter's apprenticeship at the Bureau of General Affairs and Finance of Badan Informasi Geospasial, cash management was carried out based on procedures prepared and approved by the authorities involved. The purpose of carrying out this final project is to review procedures for cash management starting from cash submission, cash disbursement, cash accountability related to disbursement/use of cash, to recording cash receipts and disbursements at the Bureau of General Affairs and Finance of the Geospatial Information Agency. The data related to cash management procedures mentioned earlier are sourced from real practices carried out at the General and Financial Bureau of Badan Informasi Geospatial. Badan Informasi Geospasial is a Non-Ministerial Government Institution coordinated under the Minister of National Development Planning. Therefore, the source of cash is not only revenue from the sale of goods and services, but also from the State Treasury. All procedures related to cash management that have been carried out at the General and Financial Bureau of Badan Informasi Geospasial are based on regulations that have been ratified and approved to be implemented. Even though this procedure was carried out properly, there were several problems related to the completeness of the documents and the ability of its human resources regarding matters relating to the implementation of procedures using digital technology Keywords : cash management, procedure